Effects of phosphorus deficiency on anatomical structures in maize (Zea mays L.) - Sarker, Bimal Chandra; Karmoker, JL; Rashid, Parveen (Bangladesh Journal of Botany, 2010)
Anatomical response of maize (Zea mays L.) to phosphorus deficiency grown in sand culture and half strength Hoagland solution revealed that phosphorus deficiency caused a decrease in diameter of the root and stem as well as thickness of the leaf. Epidermal cells of the root, stem and leaf became thickened, cortical zone of root and stem was reduced, endodermal and pericycle cells became smaller and thick walled in phosphorus deficient plants. The prominent structural changes due to phosphorus deficiency occurred in the vascular system where the vascular area is decreased with less number of xylem vessels and smaller size of the cavity. Phosphorus deficiency also resulted in decreased number and smaller sized stomata in leaves. Key words: Phosphorus deficiency; Anatomy; Maize; Zea mays L. DOI: 10.3329/bjb.v39i1.5527 Bangladesh J. Bot. 39(1): 57-60, 2010 (June)